Digitalization of public services: a phenomenological study of the meaning of information technology in increasing the quality of public services - Reski Wardani; Syarifuddin; Aini Indrijawati (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to determine the meaning of information technology in improving the quality of public services. This research is qualitative by using a phenomenological approach to understand the phenomenon comprehensively. Data collection techniques were carried out using in-depth interview techniques and direct observation of informants who took care of permits. The phenomenological data analysis technique used in this study is based on Edmund Husserl’s ideas, namely Epoche, Noema, Noesis, Intentional Analysis, and Eidetic Reduction. The results of the research show that information technology is a tool for obtaining information which is the meaning of information technology in improving service quality. From this information technology can help people to communicate and disseminate information. The next meaning of information technology such as smartphones is as a communication tool. The use of information technology as a tool for communication provides convenience. Communities can communicate long distances easily and quickly. Lifestyle is also defined as the meaning of information technology to see the existing phenomenon that the use of information technology has become very important in everyday life. People’s lifestyles are greatly influenced by the existence of technology. Starting from education, transportation, economy, even social. The various conveniences offered are one of the reasons for people to follow technological trends. Information Technology is like a valuable item, making human work easier and more efficient.